Evaluation of the Performance of Corroded Concrete with Bottom Ash and Bacteria using Resistivity and Impact Echo Techniques - Zaki, Ahmad; Azizah, Salma; P. Rosyidi, Sri Atmaja; Mahbubi, Khairil; Ibrahim, Zainah (SINERGI, 2025)
Concrete is a significant contributor to global emissions, necessitating the development of environmentally friendly alternatives. This study explores the use of reinforced concrete (RC) incorporating industrial by-products, specifically bottom ash (BA), as a partial sand replacement to address this issue. Additionally, the study examines the potential of Bacillus subtilis bacteria to enhance the self-repair capabilities of corroded RC with BA. Concrete mixtures with 10%, 20%, and 30% BA were prepared and subjected to accelerated corrosion for 48, 96, and 168 hours. The corroded RC specimens were then tested for compressive strength, flexural strength, corrosion rate, non-destructive testing (NDT) methods, and SEM analysis. NDT methods included impact echo (IE) and resistivity techniques. Results showed that increasing BA content led to a decrease in corrosion resistance, with current measurements of 2.07, 1.64, and 1.47 amperes for 10%, 20%, and 30% BA, respectively. After 168 hours of corrosion, the IE frequency of the Bacillus subtilis-treated specimens was 2561.04 Hz, the lowest among all samples, while the 30% BA specimen exhibited the highest frequency at 7924.81 Hz. Resistivity measurements after 168 hours showed lower resistivity in Bacillus subtilis-treated specimens (18.25 kΩ·cm) compared to the 20% BA specimen (29.27 kΩ·cm). These findings suggest that the addition of BA and Bacillus subtilis bacteria can reduce the corrosion risk in concrete, making it a viable alternative to traditional RC.